Insulin resistance and birth weight - Horáková, Dagmar; Janoutová, Gabriela; Janout, Vladimír (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2005)
This review article describes the scientific evidence for the relationship between birth weight and insulin resistance. Most studies demonstrate that low birth weight is closely connected to insulin resistance and later development of diabetes type II in adulthood. For this reason it is important for clinicians to focus on the personal history of the patient's birth weight. In patients with low birth weight, primary measures should be taken to prevent the development or progress of insulin resistance, and late consequences like diabetes and atherosclerotic complications.
Keywords: Infant, Low Birth Weight; rizikové faktory; Insulin Resistance; porodní hmotnost; inzulinová rezistence; Risk Factors; Diabetes Mellitus, Type 2; novorozenec s nízkou porodní hmotností; Birth Weight; lidé; Humans; diabetes mellitus 2. typu; novorozenec; Infant, Newborn